1996
DOI: 10.1016/0370-2693(95)01574-4
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive B decays as a QCD lab

Abstract: Phenomenological models of heavy flavour decays differ significantly in their predictions of global features of B c decays, like the B c lifetime or the relative weight of c → s and b → c transitions. The 1/m Q expansion which is directly based on QCD allows predictions on the pattern to be expected, namely τ (B c ) to lie well below 1 psec with c → s dominating over b → c and a reduced semileptonic branching ratio. Due to interference effects one also predicts a lower charm content in the final states of B c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 12 publications
12
41
0
Order By: Relevance
“…−0.16 ± 0.03 ps confirmed the theoretical predic-tions regarding various B c meson properties, spectroscopy, production and decay channels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: +018supporting
confidence: 63%
See 3 more Smart Citations
“…−0.16 ± 0.03 ps confirmed the theoretical predic-tions regarding various B c meson properties, spectroscopy, production and decay channels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: +018supporting
confidence: 63%
“…The calculation of the B c leptonic decay constant f Bc can be carried out either using QCD-based methods, such as lattice QCD [41], QCD sum rules [42][43][44][45], or adopting some constituent quark models [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. So far, lattice QCD has only been employed to calculate the B c purely leptonic width.…”
Section: +018mentioning
confidence: 99%
See 2 more Smart Citations
“…[38] that the lifetime of the B c meson puts severe constraint on various NP couplings. Based on various SM calculations [63][64][65] of the B c lifetime, it is found that BðB c → τνÞ cannot be more than 5%. However, this can be relaxed up to 30% depending on the input parameters that are used in the SM calculation.…”
Section: Introductionmentioning
confidence: 99%